Perceptions of barriers to cardiac rehabilitation use in Brazil - de Melo Ghisi G.L. (2013)
Cardiovascular diseases (CVD) are the leading cause of mortality in middle-income countries, such as Brazil. However, given the diversity in health care systems in Brazil, access to proven services, such as cardiac rehabilitation (CR), varies widely. Purpose: To describe and compare multilevel barriers to CR enrollment and participation in three Brazilian cohorts: (1) cardiac outpatients not attending CR (public or private system); (2) cardiac outpatients paying for CR; and (3) residents at high-risk of CVD with access to a free comprehensive exercise program but not making use of the program. Methods: Brazilian residents from two cities were invited to participate-Florianopolis, an urban center; and Luzerna, a rural center. Respondents completed a survey including the Cardiac Rehabilitation Barriers Scale. Mann-Whitney U tests were used to compare barriers between cohorts cross-sectionally. Results: Six hundred twenty-eight Brazilians consented to participate: 237 (37.7%) from Florianopolis, of which 139 (22.1%) participated in CR; and 391 (62.3%) from Luzerna. The mean total CR barriers for the sample were 1.66 ± 0.6 and differed significantly by cohort (P < 0.001). CR nonattendees from Florianopolis (eg, distance and not knowing about CR) and participants from Luzerna (eg, work and family responsibilities) reported significantly higher barriers than CR attendees from Florianopolis. Conclusion: CR nonattendees reported significantly greater barriers than CR attendees. It is hoped that the provision of CR will increase, and that the development of the programs will be in a manner which mitigates the chief barriers identified herein. © 2013 Ghisi et al.